Penggunaan Strategi Pembelajaran Berbasis Masalah (SPBM) Untuk Meningkatkan Aktivitas Mahasiswa Pada Mata Kuliah Dasar Penyelengaraan Konvensi - Tuti Hartati; . Kadunci; Tuty Herawati (SOSIALITA, 2010)
The research is aimed to apply the teaching and learning method by using studi case method. On MICE study program, one of the subjects given is the basic knowledge how to organizing convention. On the subject the students learn how to organize the convention professionally. The learning process make the students will be creative to organize one convention. The teaching and learning process use the Students Team Achievement Division (STAD) by distributing and deviding the classs or students in to small group 4-5 student in one group. It is the good method to apply on the class, because the result of research said that finally the application of case based method are able to increase the student's performance and achievement on the class. The most important thing, the lecture need to give serious attention to support the students and to give explanation what they have to do in solving the case